Other side of the canyon - Grey, Romer Zane (Curley, 1970)
A silent man who let his guns speak for him, Laramie Nelson was a seasoned Indian fighter, cowhand, shootist, and jack-of-all-trades. And although he was one of the most feared gunmen in the Old West, Nelson was a man of honor whose word was as good as his aim.
50995